Analysis of Parents' Responsibilities towards Children Who Marry Underage - Septiningsih, Ismawati (Universitas Ekasakti, 2024)
Marriage is not just about forming a bond for a man and a woman to become legal husband and wife, but has more complex aspects. Aspects of marriage also include kinship aspects and broader social aspects. Based on this, marriages should ideally be carried out by men and women who have met the minimum age limit for marriage, and parents are also obliged to protect their children so that they do not enter into underage marriages. This research aims to analyze the responsibility of parents towards children in the event of underage marriage. The research method used in writing this article is normative legal research with a statutory approach. The results of this research are positive law, Law Number 23 of 2002 concerning Child Protection as amended by Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection has provided protection in the form of criminal sanctions for people parents who allow their children to marry underage and ensnare them under child neglect provisions.